Creator Theology and Sterba's Argument from Evil - Milburn, Joe (Religions, 2022)
In this paper, I reformulate Sterba’s argument from evil and consider the various ways theists might respond to it. There are two basic families of responses. On the one hand, theists can deny that God, as a perfect being, needs to act in accordance with Sterba’s moral evil prevention requirements (MEPRs). We can call these responses exceptionalist responses. On the other hand, the theist can deny that God’s acting in accordance with the MEPRs would imply an absence of significant and especially horrendous evil consequences of immoral actions in the world. We can call these responses compatibilist responses. I argue that the availability of both sorts of responses shows that Sterba’s argument should not be taken as a logical argument from evil. A good God is logically possible. However, this does not show that Sterba’s argument fails as an evidential argument from evil. In the second section, I argue that if we work within the framework of what Jonathan Kvanvig calls Creator Theology (CT), the force of Sterba’s argument as an evidential argument is greatly weakened.